مكافحة الاتجار بالبشر عبر شبكات التواصل الاجتماعي – من واقع قضايا الاتجار بالبشر في شرطة دبي: Combating human trafficking through social networks - from the reality of human trafficking cases in Dubai Police - Al-Bannai, Hamid Ali; Qasem, Ammar Ali Abdo (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2023)
بالحديث عن جريمة الاتجار بالبشر، فإننا نقف أمام نمط جديد من العبودية فاق ما عداه من أنماط الرق القديمة من حيث الحجم والانتشار، فكلما توغلنا أكثر في سبر أغوار هذه الظاهرة، والبحث عن مكنوناتها على المستوى القانوني أو الدولي أو التاريخي، كلما كان الموقف الإنساني أكثر فظاعة وغياب للضمير. ولما أصبح من الشائع ارتياد وسائط التواصل الاجتماعي في ارتكاب العديد من الممارسات المجرمة قانوناً، ومنها جريمة الاتجار بالبشر، من خلال عدة طرق، باستخدام المواقع الإلكترونية لغرض عرض الأنشطة الإجرامية التي يتم فيها استغلال البشر، كالمواقع الخاصة بالأنشطة الجنسية التي يتم فيها عرض النشاط الإجرامي. وعليه كان لابد من الاستعانة بالمنهج الوصفي لمعرفة كيفية استخدام وسائل التواصل الاجتماعي وشبكة الإنترنت في ارتكاب جريمة الاتجار بالبشر، وأبعاد هذه الجريمة وكيفية التصدي لها، والمنهج الكيفي لدراسة حالات التعامل مع بلاغات الاتجار بالبشر وأليات مكافحة هذه الجريمة إلكترونيًا، وتوصلت النتائج إلى أن الجريمة المرتكبة عبر مواقع التواصل الاجتماعي يجعلها تتميز بخصوصيات تنفرد بها في هذا العالم الرقمي، ولابد من توافر الأركان التي تقوم عليها هذه الجريمة كالركن المادي والركن المعنوي لإيقاع الجزاء المناسب، وجاءت أهم التوصيات باستخدام تطبيقات الذكاء الاصطناعي في تطوير مكافحة جريمة الاتجار بالبشر عبر مواقع التواصل الاجتماعي.وكذا تبني تبني إستراتيجية وتدابير أمنية قائمة على المنع. ABSTRACT Speaking about the crime of human trafficking, we stand before a new type of slavery that surpasses other old types of slavery in terms of size and spread. The more we delve into exploring the depths of this phenomenon and searching for its components at the legal, international, or historical level, the more humanitarian the situation becomes. Atrocity and lack of conscience. Since it has become common to use social media to commit many legally criminal practices, including the crime of human trafficking, through several methods, using websites for the purpose of displaying criminal activities in which people are exploited, such as websites specializing in sexual activities in which criminal activity is displayed. Therefore, it was necessary to use the descriptive approach to find out how social media and the Internet are used to commit the crime of human trafficking, the dimensions of this crime and how to confront it, and the qualitative approach to study cases of dealing with reports of human trafficking and mechanisms to combat this crime electronically. The results concluded that the crime committed via... Social networking sites make them distinguished by their unique characteristics in this digital world, and the pillars upon which this crime is based must be present, such as the material pillar and the moral pillar, in order to impose the appropriate penalty. The most important recommendations came from using artificial intelligence applications in developing the fight against the crime of human trafficking through social networking sites. Adopting a prevention-based security strategy and measures.